Implementasi Alat Penetas Telur Full Otomatis Guna Meningkatkan Produksi Sektor UMKM di RAKTA FARM Desa Gelgel Klungkung - I Made Sastra Dwikiarta; I Putu Yudi Prabhadika; Ida Ayu Trisna Yudi Asri (Universitas Warmadewa, 2024)
Society in general and small entrepreneurs in particular have enormous potential to develop Micro, Small and Medium Enterprises (MSMEs). This will be one of the main factors driving the growth and development of the Indonesian economy amidst the current flow of globalization. The Community Service Partner is RAKTA FARM where this partner has a chicken farming business in Br. Tangkas, Gelgel Village - Klungkung. The problem with partners who will expand their business into the Balinese free-range chicken hatching sector is that they still use conventional methods. The Balinese Hindu community generally uses Balinese free-range chickens for religious ceremonies and for personal consumption. The methods that will be used in implementing this Community Service are interview methods, face-to-face methods, and workshops on how to use/operate fully automatic egg incubators. The solution that will be implemented is to increase the chicken population relatively quickly and ensure the availability of seeds for continuous production. The fact is that automatic hatching machines help parents hatch eggs to produce chicks. Hatching with a hatching machine can also increase the production scale and hatchability of eggs because the environmental temperature and humidity can be regulated precisely at RAKTA FARM Br. Tangkas, Gelgel Village - Klungkung.